Misalignment in supervision: implementing risk/needs assessment instruments in probation - Viglione, Jill (Criminal justice and behavior, 2015)
Risk and needs assessment (RNA) tools are well regarded as a critical component of a community corrections organization implementing evidence-based practices (EBPs), given the potential impact of using such tools on offender-level and system outcomes. The current study examines how probation officers (POs) use a validated RNA tool in two adult probation settings. Using interview and observational data, this study explores how POs use an assessment tool during all facets of their work from preplanning, routine administrative tasks, and face-to-face case management interactions with probation clients. Findings suggest POs overwhelmingly administer the RNA tool, but rarely link the RNA scores to key case management or supervision decisions. These findings highlight some of the challenges and complexities associated with the application of RNA tools in everyday practice. Study implications emphasize the need to modify current probation practices to create a synergy between the RNA and related supervision practices. Findings from this study contribute to a better appreciation for how the new penology integrates risk management with client-centered case models to improve outcomes.